Prediction of bladder outcomes after traumatic spinal cord injury: a longitudinal cohort study - Pavese, Chiara; Weidner, Norbert; Rupp, Rüdiger (PLoS medicine, 2016)
Thomas Kessler and colleagues identify and validate two models to predict urinary continence and complete bladder emptying one year after traumatic spinal cord injury.